Carrots and Related Vegetable Umbelliferae - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
V E Rubatzky and C F Quiros (Department of Vegetable Crops, University of California, USA), and P W Simon (USDA-ARS, University of Wisconsin, USA). CABI. 1999. 304 pp.ISBN 0851991297.£27.50 $50.00 Euro 48.10(See earlier CABI reference for...